Tokyo ESP. 5 - Segawa, Hajime (Vertical, Inc., 2016)
"Rinka, who had gone missing, arrives back in Tokyo to put a stop to the plans of a terrorist organization that threatens Tokyo with a dangerous weapon, and rescue Ren and Marume from their evil clutches. But where had Rinka been that whole time? And what had she been doing? The truth is darker than the White Girl could have imagined ..."--Cover.